A flexible electrolyte and its preparation method and application
By using polymers containing polar groups and ionic liquids containing transition metal salts, the problems of ammonia sensor leakage and shell swelling are solved, miniaturization and cost reduction are achieved.
Patent Information
- Application Number
- CN202311459815.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-11-09
- Filing Date
- 2023-11-03
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-11-03
AI Technical Summary
The existing ammonia sensors have problems of liquid leakage and shell swelling, and are costly and difficult to achieve miniaturization.
The polymer frame is prepared using polymers containing polar groups and immersed by ionic liquid dissolving transition metal salts to form a flexible electrolyte with a high-density microscopic surface and a three-dimensional network structure. The flexible electrolyte has self-supporting properties, can be well bonded to the electrodes, and realizes direct transfer.
The ammonia sensor is miniaturized, avoiding liquid leakage and shell swelling problems. At the same time, the solubility and response sensitivity of the electrolyte are improved by adding transition metal salts, reducing the cost of use.
Smart Images

Figure CN117470934B_ABST
Abstract
Description
[0001] This application claims the priority of the Chinese patent application filed with the China Patent Office on November 9, 2022, with application number 202211399750.1 and invention name “Flexible electrolyte and its preparation method and application”, all contents of which are cited in this application. Technical Field
[0002] The present invention belongs to the technical field of sensors, and in particular relates to a flexible electrolyte and a preparation method and application thereof. Background Art
[0003] Electrochemical ammonia sensor is a common gas concentration detection device. Its working principle is that when ammonia diffuses to the working electrode, it loses electrons at the solid-liquid-gas three-phase interface and undergoes oxidation reaction to generate N2 / NO x , generate mobile ions or change the composition of the electrolyte, causing the active substances in the electrolyte to receive electrons at the counter electrode and undergo a reduction reaction. The size of the electrical signal of the entire reaction is proportional to the ammonia concentration. Therefore, the size of the electrical signal of the ammonia sensor can be used to quantitatively test the ammonia content in the environment. In order to avoid the volume change of the electrolyte at different humidity, the existing ammonia sensors usually use non-volatile ionic liquids as the main component of the electrolyte, but still do not solve the problems of leakage and shell rupture. At the same time, in order to make it have a more ideal response signal, a variety of ionic liquids and graphene are often added to the electrolyte, resulting in a higher cost of the ammonia sensor.
[0004] In order to reduce costs and solve the problems of leakage and shell bulging, existing research has used flexible solid electrolytes such as ionic liquid gel as electrolytes for ammonia sensors. The principle is to use ionic liquids containing unsaturated chemical bonds as monomers, which are polymerized and form a three-dimensional network through the interaction between molecular chains to obtain flexible materials. The ionic liquid is fixed inside the electrolyte through interaction, thereby eliminating the problems of leakage and shell bulging. However, the ammonia sensor structure obtained by the common preparation method of flexible electrolytes is relatively bloated and difficult to miniaturize. Summary of the invention
[0005] In order to achieve the above object, the technical solution adopted by the present invention is: a method for preparing a flexible electrolyte, the specific steps comprising: dissolving, molding and drying a polymer containing a polar group to prepare a polymer framework, soaking the polymer framework in an ionic liquid dissolved with a transition metal salt until absorption equilibrium is reached, and obtaining a flexible electrolyte;
[0006] The polar group-containing polymer includes a carboxyl-containing polymer, a hydroxyl-containing polymer, and a cyano-containing polymer.
[0007] Based on the above, the mass ratio of the polar group-containing polymer, the ionic liquid, and the transition metal salt is 100:20-80:0.02-16.
[0008] Based on the above, the polar group-containing polymer includes hydroxyethyl cellulose, hydroxypropyl cellulose, cellulose acetate, PAA, and PMAA.
[0009] Based on the above, the transition metal salt includes a Mn-containing salt that can reversibly coordinate with NH3. 2+ , Cu 2+ 、Ni 2+ 、Zn 2+ 、Ag + 、Co 2+ of inorganic salts.
[0010] Based on the above, the ionic liquid is 1-ethyl-3-methylimidazole thiocyanate, 1-propyl-3-methylimidazole thiocyanate, 1-butyl-3-methylimidazole thiocyanate, 1-hexyl-3-methylimidazole thiocyanate, 1-octyl-3-methylimidazole thiocyanate, 1-decyl-3-methylimidazole thiocyanate, 1-dodecyl-3-methylimidazole thiocyanate, 1-tetradecyl-3-methylimidazole thiocyanate, 1-hexadecyl-3-methylimidazole thiocyanate, 1-butyl-2,3-dimethylimidazole thiocyanate, 1-vinyl-3-propyl imidazole thiocyanate, 1-vinyl-3-butyl imidazole thiocyanate, 1-vinyl-3-benzyl imidazole thiocyanate, 1-ethyl-3-methylimidazole cyanamide, 1-butyl-3-methyl The invention relates to imidazolium ions, such as 1-butyl-3-methylimidazole dicyandiamide, 1-ethyl-3-methylimidazole hydrogen sulfate, 1-butyl-3-methylimidazole hydrogen sulfate, 1-hexyl-3-methylimidazole hydrogen sulfate, 1-butyl-2,3-dimethylimidazole hydrogen sulfate, 1-hexyl-2,3-dimethylimidazole hydrogen sulfate, 1-methylimidazole hydrogen sulfate, 1-ethylimidazole hydrogen sulfate, 1-butylimidazole hydrogen sulfate, 1-hexylimidazole hydrogen sulfate, 1-vinyl-3-propylimidazole hydrogen sulfate, 1-vinyl-3-butylimidazole hydrogen sulfate or 1-hydroxyethyl-3-methylimidazole hydrogen sulfate, and the like, including imidazolium ion cations containing one or more alkyl side chains with a length of less than or equal to 16 carbons, and anions containing hydrophilic polar groups.
[0011] Based on the above, the polar group-containing polymer is hydroxypropyl cellulose, and the ionic liquid is 1-ethyl-3-methylimidazole thiocyanate;
[0012] The steps of preparing the polymer framework include: dissolving the hydroxypropyl cellulose in an ethanol solvent, stirring overnight to obtain a polymer framework precursor, and then pouring the polymer framework precursor into a mold to remove the ethanol solvent through a supercritical carbon dioxide drying method to obtain the polymer framework.
[0013] The present invention also provides a flexible electrolyte, which is prepared according to the above preparation method, and is a self-supporting, deformable flexible membrane. The flexible electrolyte interacts with the electrode to have good adhesion, thereby achieving direct transfer.
[0014] The present invention also provides an integrated electrode electrolyte, which comprises the above-mentioned flexible electrolyte and an electrode arranged on the surface of the flexible electrolyte by a thermal transfer process.
[0015] The present invention also provides a use of the above-mentioned flexible electrolyte or the above-mentioned integrated electrode electrolyte in the preparation of an ammonia electrochemical gas sensor.
[0016] The present invention also provides an ammonia electrochemical gas sensor comprising the above-mentioned flexible electrolyte, characterized in that it includes a bottom shell, an upper shell arranged on the top of the bottom shell, a rigid support partition arranged inside the bottom shell, and the flexible electrolyte arranged on the rigid support partition, the upper surface of the flexible electrolyte is provided with a working electrode, the lower surface of the flexible electrolyte is provided with a counter electrode alone or with a counter electrode and a reference electrode at the same time, conductive through holes are respectively opened on the upper shell, the rigid support partition and the bottom shell, the working electrode is connected to an electrode welding sheet through a wire, and a dustproof film is provided on the top of the upper shell.
[0017] Specifically, the preparation steps of the ammonia electrochemical gas sensor include: adding a dispersant to a noble metal catalyst to form a slurry, printing the slurry on the surface of a hydrophobic breathable membrane, and sintering the slurry to obtain a hydrophobic breathable membrane containing a working electrode, a counter electrode, and a reference electrode, and using a thermal transfer process to transfer the working electrode to the upper surface of a flexible electrolyte, and the counter electrode and the reference electrode to the lower surface of the flexible electrolyte, respectively, to obtain an electrode-electrolyte integrated structure, wherein the sensor working electrode is combined with the upper surface of the flexible electrolyte, and the working electrode is connected to the electrode welding sheet through a metal wire. The counter electrode and the reference electrode are combined with the lower surface of the flexible electrolyte, and the counter electrode and the reference electrode are distributed on the same vertical line as the through hole of the rigid support partition and the conductive through hole of the bottom shell, and it is ensured that the through hole area of the rigid support partition is larger than the conductive through hole of the bottom shell.
[0018] The present invention has outstanding substantial characteristics and significant progress relative to the prior art. Specifically, the present invention first uses a polymer containing a polar group to prepare a polymer framework structure, and then selects an ionic liquid that can interact with the polymer framework structure, and utilizes the anions and cations in the ionic liquid to interact with the functional groups on the main chain and side chain of the polymer framework to produce dynamic interactions, thereby absorbing the ionic liquid into the polymer framework, and finally generating a flexible electrolyte with a high-density microscopic surface and a three-dimensional network structure and good internal uniformity of the material. The flexible electrolyte belongs to a semi-solid electrolyte, which is a membrane with self-supporting properties, and can interact with the electrodes to make it have good adhesion, and can realize direct transfer, so that the electrodes can be transferred to the flexible electrolyte surface by a thermal transfer process, and an integrated electrode electrolyte structure is obtained, and finally the integrated electrode electrolyte structure is assembled into an ammonia electrochemical sensor, thereby achieving the purpose of miniaturization of the ammonia sensor.
[0019] Furthermore, by adding transition metal salts to the ionic liquid, the coordination effect of the transition metal salts can be utilized to effectively increase the solubility of the electrolyte for ammonia, stabilize the physically dissolved ammonia in the electrolyte, and improve current attenuation. The coordination effect of the transition metal and ammonia is reversible, so that the prepared ammonia sensor is a non-consumable ammonia electrochemical sensor, thereby reducing the cost of use. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The infrared spectra of the flexible electrolyte prepared by the present invention and the raw materials of 1-ethyl-3-methylimidazole thiocyanate and hydroxypropyl cellulose;
[0021] Figure 2 This is an optical microscope photo of the hydroxypropyl cellulose raw material in the present invention;
[0022] Figure 3 This is an optical microscope photograph of the flexible electrolyte prepared in Example 1 of the present invention;
[0023] Figure 4 The curve showing the change of the response current and time of the ammonia sensor prepared in Example 1 of the present invention in an ammonia atmosphere;
[0024] Figure 5 The curve showing the change of the response current and time of the ammonia sensor prepared in Example 2 of the present invention in an ammonia atmosphere;
[0025] Figure 6 The curve showing the change of the response current and time of the ammonia sensor prepared in Example 3 of the present invention in an ammonia atmosphere;
[0026] Figure 7The curve showing the change of the response current and time of the ammonia sensor prepared in Example 6 of the present invention in an ammonia atmosphere;
[0027] Figure 8 The curve showing the change of the response current and time of the ammonia sensor prepared in Example 7 of the present invention in an ammonia atmosphere;
[0028] Fig. 9 The curve showing the change of the response current and time of the ammonia sensor prepared in Example 8 of the present invention in an ammonia atmosphere;
[0029] Fig.10 The curve showing the change of the response current and time of the ammonia sensor prepared in Example 9 of the present invention in an ammonia atmosphere;
[0030] Fig.11 A curve showing the change in response current and time of the ammonia sensor provided in Comparative Example 1 of the present invention when the sensor is in an ammonia atmosphere;
[0031] Fig.12 A schematic diagram of the disassembled structure of the ammonia sensor provided in Example 1 of the present invention;
[0032] Fig.13 A schematic diagram of the disassembled structure of the ammonia sensor provided in Example 2 of the present invention;
[0033] Fig.14 A schematic diagram of the disassembled structure of the ammonia sensor provided in Example 4 of the present invention;
[0034] Fig.15 A schematic diagram of the disassembled structure of the ammonia sensor provided in Example 5 of the present invention;
[0035] Fig.16 This is a photo of the flexible electrolyte prepared in Example 1 of the present invention;
[0036] In the figure: 1. Dust-proof film; 2. Upper shell; 3. Working electrode; 4. Flexible electrolyte; 5. Counter electrode; 6. Reference electrode; 7. Rigid supporting partition; 8. Metal wire; 9. Bottom shell; 10. Electrode welding sheet. DETAILED DESCRIPTION
[0037] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Example 1
[0039] This embodiment provides a method for preparing a flexible electrolyte, which specifically comprises the following steps: pouring 10 g of hydroxypropyl cellulose into 120 mL of ethanol solvent and stirring overnight to obtain a polymer framework precursor; then pouring the polymer framework precursor into a mold and evaporating part of the solvent to obtain a gel-like substance. The gel-like substance is transferred to a molding device and the ethanol is removed by supercritical carbon dioxide drying to obtain a polymer framework.
[0040] 0.025 g of CuSCN is dissolved in 2.5 g of 1-ethyl-3-methylimidazole thiocyanate to obtain a mixed solution, and the mixed solution is used to soak the polymer framework to achieve absorption equilibrium to obtain a flexible electrolyte. In this embodiment, the soaking time is 24 hours.
[0041] This embodiment also provides a flexible electrolyte, which is prepared according to the method for preparing a flexible electrolyte.
[0042] Infrared spectrum observation:
[0043] In order to verify that the flexible electrolyte has stable binding force inside, hydroxypropyl cellulose (HPC), 1-ethyl-3-methylimidazole thiocyanate and the prepared flexible electrolyte were characterized by infrared spectroscopy. The results are as follows Figure 1 As shown. Figure 1 It can be seen that:
[0044] In the characteristic curve of HPC, 2930cm -1 2860cm is the stretching vibration absorption peak of methyl and methylene in the side chain; -1 3454cm is the stretching vibration absorption peak of methyl and methylene in glucose monomer; -1 1466cm is the hydroxyl stretching vibration absorption peak; -1 It is the deformation vibration absorption peak of CH, 1000~1300cm -1 It is the stretching vibration absorption peak of the ether bond connected to the glucose monomer.
[0045] In the characteristic curve of 1-ethyl-3-methylimidazolium thiocyanate, 3090cm -1 The peak at 2046 cm is attributed to the CH stretching vibration peak on the imidazole ring. -1 Belong to SCN - Stretching vibration peak, 1568cm -1 With 1463cm -1 It is the stretching vibration absorption peak of C=N in the imidazole ring, 1165cm -1 It is the absorption peak of the CH in-plane deformation vibration on the imidazole ring.
[0046] In the flexible electrolyte, i.e., the flexible electrolyte characteristic curve, due to the formation of hydrogen bonds, the characteristic peak position of the hydroxyl group in HPC changes from 3454 cm -1 The displacement is 3415cm -1 After the dynamic interaction between HPC and ionic liquid, the vibration state of methyl and methylene groups in the glucose monomer inside it changes, so its -1 With 2860cm -1 The intensity of the vibration characteristic peak at is greatly weakened.
[0047] In summary, the reason why HPC and ionic liquids can form a stable flexible electrolyte is that the hydroxyl groups in the polymer chain form dynamic interactions such as hydrogen bonds and van der Waals forces with the characteristic groups in the anions and cations.
[0048] like Fig.16 As shown in the figure, it is a photo of the flexible electrolyte prepared in this embodiment. It can be seen from the figure that the flexible electrolyte is a gel film structure with a relatively uniform structure and a certain degree of flexibility. At the same time, the color of the flexible electrolyte will also be affected by the color of the absorbed ionic liquid. For example, the flexible electrolyte prepared in this embodiment uses 1-ethyl-3-methylimidazolium thiocyanate as the ionic liquid, so the appearance is yellow.
[0049] This embodiment also provides an integrated electrode electrolyte, which includes the above-mentioned hydroxypropyl cellulose-based electrolyte and an electrode arranged on the surface of the flexible electrolyte by a thermal transfer process.
[0050] This embodiment also provides an application of the above-mentioned flexible electrolyte and the above-mentioned integrated electrode electrolyte, and the flexible electrolyte and the integrated electrode electrolyte can be used to prepare an ammonia electrochemical gas sensor.
[0051] Optical microscope observation:
[0052] The surface morphology of hydroxypropyl cellulose raw material and flexible electrolyte was characterized by optical microscopy. Figure 2 and Figure 3 As shown. Figure 2 It can be seen that the hydroxypropyl cellulose-based fibers are independent of each other and do not have good intermolecular interactions. However, after the introduction of 1-ethyl-3-methylimidazole thiocyanate, its anions and cations can interact non-covalently with the functional groups on the main chain and side chain of hydroxypropyl cellulose. Figure 3 It can be seen that the flexible electrolyte has a continuous and high-density microscopic surface morphology. These conditions prove that the flexible electrolyte has a high-density three-dimensional network structure and good internal uniformity of the material, which further illustrates that hydroxypropyl cellulose can interact with ionic liquids to form hydrogen bonds and van der Waals forces.
[0053] This embodiment also provides an ammonia electrochemical gas sensor, which is prepared by using the flexible electrolyte.
[0054] Specifically, Fig.12 As shown, the ammonia electrochemical gas sensor provided in this embodiment includes a bottom shell 9, an upper shell 2 arranged on the top of the bottom shell 9, the hard support partition 7 arranged inside the bottom shell 9, and a flexible electrolyte 4 arranged on the hard support partition 7. A working electrode 3 is arranged on the upper surface of the flexible electrolyte 4, and a counter electrode 5 and a reference electrode 6 are arranged on the lower surface of the flexible electrolyte 4. Conductive through holes are respectively provided on the upper shell 2, the hard support partition 7 and the bottom shell 9. The working electrode 3 is connected to an electrode welding sheet 10 through a metal wire 8. A dustproof film 1 is provided on the top of the upper shell 2. Among them, the bottom shell and the upper shell are both cylindrical, the working electrode is circular, and the counter electrode and the reference electrode are both semicircular.
[0055] Specifically, the preparation steps of the ammonia electrochemical gas sensor include: adding a dispersant to a precious metal catalyst to form a slurry, printing the slurry onto the surface of a hydrophobic breathable membrane, and sintering the slurry to obtain a hydrophobic breathable membrane containing a working electrode, a counter electrode, and a reference electrode, and using a thermal transfer process to transfer the working electrode to the upper surface of a flexible electrolyte, and to transfer the counter electrode and the reference electrode to the lower surface of the flexible electrolyte, respectively, to obtain an electrode-electrolyte integrated structure. The sensor working electrode is bonded to the upper surface of the flexible electrolyte, and the working electrode is connected to the electrode welding sheet by a metal wire. The counter electrode and the reference electrode are bonded to the lower surface of the flexible electrolyte, and the counter electrode and the reference electrode are distributed on the same vertical line as the through hole of the rigid support partition and the conductive through hole of the bottom shell, and it is ensured that the through hole area of the rigid support partition is larger than the conductive through hole of the bottom shell.
[0056] Specifically, this embodiment uses hydroxypropyl cellulose to prepare a hydroxypropyl cellulose polymer framework structure, and then uses the hydroxypropyl cellulose polymer framework structure to interact with the ionic liquid, and uses the anions and cations in 1-ethyl-3-methylimidazole thiocyanate to non-covalently interact with the functional groups on the main chain and side chain of hydroxypropyl cellulose to generate a flexible electrolyte with a specific high-density microscopic surface, a high-density three-dimensional network structure and good internal uniformity of the material.
[0057] The flexible electrolyte is a membrane with self-supporting properties. The electrode is then transferred to the surface of the flexible electrolyte using a thermal transfer process to obtain an integrated electrode-electrolyte structure, which is then assembled into an electrochemical sensor and responds to the target gas, thereby achieving the purpose of miniaturization of the ammonia sensor.
[0058] Furthermore, by adding transition metal salt CuSCN to 1-ethyl-3-methylimidazole thiocyanate, the coordination effect of the transition metal salt is used to effectively increase the solubility of the electrolyte to ammonia, stabilize the physically dissolved ammonia in the electrolyte, and improve the current attenuation. Moreover, the coordination effect between the transition metal and ammonia is reversible, so that the sensor prepared belongs to a non-consumable ammonia electrochemical sensor.
[0059] Example 2
[0060] This embodiment provides a method for preparing a flexible electrolyte, which specifically comprises the following steps: pouring 10 g of hydroxypropyl cellulose into 120 mL of ethanol solvent and stirring overnight to obtain a polymer framework precursor; then pouring the polymer framework precursor into a mold and evaporating part of the solvent to obtain a gel-like substance. The gel-like substance is transferred to a molding device and the ethanol is removed by supercritical carbon dioxide drying to obtain a polymer framework.
[0061] 0.05 g of CuSCN is dissolved in 2.5 g of 1-ethyl-3-methylimidazole thiocyanate to obtain a mixed solution, and the mixed solution is used to soak the polymer framework to achieve absorption equilibrium to obtain a flexible electrolyte. In this embodiment, the soaking time is 24 hours.
[0062] This embodiment also provides a flexible electrolyte, which is prepared according to the method for preparing a flexible electrolyte.
[0063] This embodiment also provides an application of the above-mentioned flexible electrolyte, which can be used to prepare an ammonia electrochemical gas sensor.
[0064] This embodiment also provides an ammonia electrochemical gas sensor, which is prepared by using the flexible electrolyte.
[0065] Specifically, the ammonia electrochemical gas sensor provided in this embodiment is as follows Fig. 9 As shown, it includes a bottom shell 9, an upper shell 2 arranged on the top of the bottom shell 9, the hard support partition 7 arranged inside the bottom shell 9, and a flexible electrolyte 4 arranged on the hard support partition 7. A working electrode 3 is arranged on the upper surface of the flexible electrolyte 4, and a counter electrode 5 and a reference electrode 6 are arranged on the lower surface of the flexible electrolyte 4. Conductive through holes are respectively provided on the upper shell 2, the hard support partition 7 and the bottom shell 9. The working electrode 3 is connected to an electrode welding sheet 10 through a metal wire 8. A dustproof film 1 is provided on the top of the upper shell 2. Among them, the bottom shell and the upper shell are both rectangular, the working electrode is rectangular, and the counter electrode and the reference electrode are both rectangular.
[0066] Specifically, the preparation steps of the ammonia electrochemical gas sensor include: adding a dispersant to a precious metal catalyst to form a slurry, printing the slurry onto the surface of a hydrophobic breathable membrane, and sintering the slurry to obtain a hydrophobic breathable membrane containing a working electrode, a counter electrode, and a reference electrode, and using a thermal transfer process to transfer the working electrode to the upper surface of a flexible electrolyte, and to transfer the counter electrode and the reference electrode to the lower surface of the flexible electrolyte, respectively, to obtain an electrode-electrolyte integrated structure. The sensor working electrode is bonded to the upper surface of the flexible electrolyte, and the working electrode is connected to the electrode welding sheet by a metal wire. The counter electrode and the reference electrode are bonded to the lower surface of the flexible electrolyte, and the counter electrode and the reference electrode are distributed on the same vertical line as the through hole of the rigid support partition and the conductive through hole of the bottom shell, and it is ensured that the through hole area of the rigid support partition is larger than the conductive through hole of the bottom shell.
[0067] Example 3
[0068] This embodiment provides a method for preparing a flexible electrolyte, which specifically comprises the following steps: pouring 10 g of hydroxypropyl cellulose into 120 mL of ethanol solvent and stirring overnight to obtain a polymer framework precursor; then pouring the polymer framework precursor into a mold and evaporating part of the solvent to obtain a gel-like substance. The gel-like substance is transferred to a molding device and the ethanol is removed by supercritical carbon dioxide drying to obtain a polymer framework.
[0069] 0.1 g of CuSCN is dissolved in 2.5 g of 1-ethyl-3-methylimidazole thiocyanate to obtain a mixed solution, and the mixed solution is used to soak the polymer framework to achieve absorption equilibrium to obtain a flexible electrolyte. In this embodiment, the soaking time is 24 hours.
[0070] This embodiment also provides a flexible electrolyte, which is prepared according to the method for preparing a flexible electrolyte.
[0071] This embodiment also provides an application of the above-mentioned flexible electrolyte, which can be used to prepare an ammonia electrochemical gas sensor.
[0072] This embodiment also provides an ammonia electrochemical gas sensor, which is prepared by using the flexible electrolyte.
[0073] Specifically, the structure of the ammonia electrochemical gas sensor provided in this embodiment is the same as that in Embodiment 1.
[0074] Specifically, the preparation steps of the ammonia electrochemical gas sensor include: adding a dispersant to a precious metal catalyst to form a slurry, printing the slurry onto the surface of a hydrophobic breathable membrane, and sintering the slurry to obtain a hydrophobic breathable membrane containing a working electrode, a counter electrode, and a reference electrode, and using a thermal transfer process to transfer the working electrode to the upper surface of a flexible electrolyte, and to transfer the counter electrode and the reference electrode to the lower surface of the flexible electrolyte, respectively, to obtain an electrode-electrolyte integrated structure. The sensor working electrode is bonded to the upper surface of the flexible electrolyte, and the working electrode is connected to the electrode welding sheet by a metal wire. The counter electrode and the reference electrode are bonded to the lower surface of the flexible electrolyte, and the counter electrode and the reference electrode are distributed on the same vertical line as the through hole of the rigid support partition and the conductive through hole of the bottom shell, and it is ensured that the through hole area of the rigid support partition is larger than the conductive through hole of the bottom shell.
[0075] Example 4
[0076] The difference between this embodiment and embodiment 1 is that the structure of the ammonia electrochemical gas sensor prepared in this embodiment is as follows: Fig.14 As shown, it is a cylindrical two-electrode NH3 sensor.
[0077] Specifically, it includes a bottom shell 9, an upper shell 2 arranged on the top of the bottom shell 9, the hard support partition 7 arranged inside the bottom shell 9, and a flexible electrolyte 4 arranged on the hard support partition 7. A working electrode 3 is arranged on the upper surface of the flexible electrolyte 4, and a counter electrode 5 is arranged on the lower surface of the flexible electrolyte 4. Conductive through holes are respectively provided on the upper shell 2, the hard support partition 7 and the bottom shell 9. The working electrode 3 is connected to an electrode welding sheet 10 through a metal wire 8. A dustproof film 1 is arranged on the top of the upper shell 2. Among them, the bottom shell and the upper shell are both cylindrical, the working electrode is circular, and the counter electrode is semicircular.
[0078] Example 5
[0079] The difference between this embodiment and embodiment 2 is that the structure of the ammonia electrochemical gas sensor prepared in this embodiment is as follows: Fig.15 As shown, a rectangular two-electrode NH3 sensor is shown.
[0080] Specifically, the ammonia electrochemical gas sensor provided in this embodiment includes a bottom shell 9, an upper shell 2 arranged on the top of the bottom shell 9, the rigid support partition 7 arranged inside the bottom shell 9, and a flexible electrolyte 4 arranged on the rigid support partition 7. A working electrode 3 is arranged on the upper surface of the flexible electrolyte 4, and a counter electrode 5 is arranged on the lower surface of the flexible electrolyte 4. Conductive through holes are respectively provided on the upper shell 2, the rigid support partition 7 and the bottom shell 9. The working electrode 3 is connected to an electrode welding sheet 10 through a metal wire 8. A dustproof film 1 is provided on the top of the upper shell 2. Among them, the bottom shell and the upper shell are both rectangular, the working electrode is rectangular, and the counter electrode is rectangular.
[0081] Example 6
[0082] This embodiment 6 provides a method for preparing a flexible electrolyte, and the specific steps include: pouring 10g of hydroxypropyl cellulose into 120mL of ethanol solvent and stirring overnight to obtain a polymer framework precursor; then pouring the polymer framework precursor into a mold and evaporating part of the solvent to obtain a gel-like substance. The gel-like substance is transferred to a molding device and the ethanol is removed by supercritical carbon dioxide drying to obtain a polymer framework;
[0083] 0.1 g of CuSCN was dissolved in 1 g of 1-ethyl-3-methylimidazole thiocyanate to obtain a mixed solution, and the obtained polymer framework was soaked in the mixed solution to achieve absorption equilibrium to obtain a flexible electrolyte. In this embodiment 6, the soaking time was 24 hours.
[0084] This embodiment also provides a flexible electrolyte, which is prepared according to the method for preparing a flexible electrolyte.
[0085] This embodiment also provides an application of the above-mentioned flexible electrolyte, which can be used to prepare an ammonia electrochemical gas sensor.
[0086] This embodiment also provides an ammonia electrochemical gas sensor, which is prepared by using the flexible electrolyte.
[0087] Specifically, the structure of the ammonia electrochemical gas sensor provided in this embodiment 6 is the same as that of embodiment 1. Specifically, it includes a bottom shell 9, an upper shell 2 arranged on the top of the bottom shell 9, the hard support partition 7 arranged inside the bottom shell 9, and a flexible electrolyte 4 arranged on the hard support partition 7. A working electrode 3 is arranged on the upper surface of the flexible electrolyte 4. A counter electrode 5 is arranged alone on the lower surface of the flexible electrolyte 4, or a counter electrode 5 and a reference electrode 6 are arranged at the same time. Conductive through holes are respectively provided on the upper shell 2, the hard support partition 7 and the bottom shell 9, and the working electrode 3 is connected to an electrode welding sheet 10 through a wire. A dustproof film 1 is arranged on the top of the upper shell 2. Among them, the bottom shell 9 and the upper shell 2 are both cylindrical, the working electrode is circular, and the counter electrode and the reference electrode are both semicircular.
[0088] Specifically, the preparation steps of the ammonia electrochemical gas sensor include: adding a dispersant to a precious metal catalyst to form a slurry, printing the slurry onto the surface of a hydrophobic breathable membrane, and sintering the slurry to obtain a hydrophobic breathable membrane containing a working electrode, a counter electrode, and a reference electrode, and using a thermal transfer process to transfer the working electrode to the upper surface of a flexible electrolyte, and to transfer the counter electrode and the reference electrode to the lower surface of the flexible electrolyte, respectively, to obtain an electrode-electrolyte integrated structure. The sensor working electrode is bonded to the upper surface of the flexible electrolyte, and the working electrode is connected to the electrode welding sheet by a metal wire. The counter electrode and the reference electrode are bonded to the lower surface of the flexible electrolyte, and the counter electrode and the reference electrode are distributed on the same vertical line as the through hole of the rigid support partition and the conductive through hole of the bottom shell, and it is ensured that the through hole area of the rigid support partition is larger than the conductive through hole of the bottom shell.
[0089] Example 7
[0090] This embodiment 7 provides a method for preparing a flexible electrolyte, which specifically comprises the following steps: pouring 10 g of hydroxypropyl cellulose into 120 mL of ethanol solvent and stirring overnight to obtain a polymer framework precursor; then pouring the polymer framework precursor into a mold and evaporating part of the solvent to obtain a gel-like substance. The gel-like substance is transferred to a molding device and the ethanol is removed by supercritical carbon dioxide drying to obtain a polymer framework.
[0091] 0.1 g of CuSCN was dissolved in 4 g of 1-ethyl-3-methylimidazole thiocyanate to obtain a mixed solution, and the obtained polymer framework was soaked in the mixed solution to achieve absorption equilibrium to obtain a flexible electrolyte. In this embodiment 7, the soaking time was 24 hours.
[0092] This embodiment also provides a flexible electrolyte, which is prepared according to the method for preparing a flexible electrolyte.
[0093] This embodiment also provides an application of the above-mentioned flexible electrolyte, which can be used to prepare an ammonia electrochemical gas sensor.
[0094] This embodiment also provides an ammonia electrochemical gas sensor, which is prepared by using the flexible electrolyte.
[0095] Specifically, the structure of the ammonia electrochemical gas sensor provided in this embodiment 7 is the same as that of embodiment 1. Specifically, it includes a bottom shell 9, an upper shell 2 arranged on the top of the bottom shell 9, the rigid support partition 7 arranged inside the bottom shell 9, and a flexible electrolyte 4 arranged on the rigid support partition 7. A working electrode 3 is arranged on the upper surface of the flexible electrolyte 4. A counter electrode 5 is arranged alone on the lower surface of the flexible electrolyte 4, or a counter electrode 5 and a reference electrode 6 are arranged at the same time. Conductive through holes are respectively provided on the upper shell 2, the rigid support partition 7 and the bottom shell 9, and the working electrode 3 is connected to an electrode welding sheet 10 through a wire. A dustproof film 1 is arranged on the top of the upper shell 2. Among them, the bottom shell 9 and the upper shell 2 are both cylindrical, the working electrode is circular, and the counter electrode and the reference electrode are both semicircular.
[0096] Specifically, the preparation steps of the ammonia electrochemical gas sensor include: adding a dispersant to a precious metal catalyst to form a slurry, printing the slurry onto the surface of a hydrophobic breathable membrane, and sintering the slurry to obtain a hydrophobic breathable membrane containing a working electrode, a counter electrode, and a reference electrode, and using a thermal transfer process to transfer the working electrode to the upper surface of a flexible electrolyte, and to transfer the counter electrode and the reference electrode to the lower surface of the flexible electrolyte, respectively, to obtain an electrode-electrolyte integrated structure. The sensor working electrode is bonded to the upper surface of the flexible electrolyte, and the working electrode is connected to the electrode welding sheet by a metal wire. The counter electrode and the reference electrode are bonded to the lower surface of the flexible electrolyte, and the counter electrode and the reference electrode are distributed on the same vertical line as the through hole of the rigid support partition and the conductive through hole of the bottom shell, and it is ensured that the through hole area of the rigid support partition is larger than the conductive through hole of the bottom shell.
[0097] Example 8
[0098] This embodiment 8 provides a method for preparing a flexible electrolyte, which specifically comprises the following steps: pouring 10 g of hydroxypropyl cellulose into 120 mL of ethanol solvent and stirring overnight to obtain a polymer framework precursor; then pouring the polymer framework precursor into a mold and evaporating part of the solvent to obtain a gel-like substance. The gel-like substance is transferred to a molding device and the ethanol is removed by supercritical carbon dioxide drying to obtain a polymer framework.
[0099] 0.1 g of Ni(SCN)2 was dissolved in 2.5 g of 1-ethyl-3-methylimidazole thiocyanate to obtain a mixed solution, and the mixed solution was used to soak the polymer framework to achieve absorption equilibrium to obtain a flexible electrolyte. In this embodiment 8, the soaking time was 24 hours.
[0100] This embodiment also provides a flexible electrolyte, which is prepared according to the method for preparing a flexible electrolyte.
[0101] This embodiment also provides an application of the above-mentioned flexible electrolyte, which can be used to prepare an ammonia electrochemical gas sensor.
[0102] This embodiment also provides an ammonia electrochemical gas sensor, which is prepared by using the flexible electrolyte.
[0103] Specifically, the structure of the ammonia electrochemical gas sensor provided in this embodiment is the same as that in Embodiment 1.
[0104] Specifically, the preparation steps of the ammonia electrochemical gas sensor include: adding a dispersant to a precious metal catalyst to form a slurry, printing the slurry onto the surface of a hydrophobic breathable membrane, and sintering the slurry to obtain a hydrophobic breathable membrane containing a working electrode, a counter electrode, and a reference electrode, and using a thermal transfer process to transfer the working electrode to the upper surface of a flexible electrolyte, and to transfer the counter electrode and the reference electrode to the lower surface of the flexible electrolyte, respectively, to obtain an electrode-electrolyte integrated structure. The sensor working electrode is bonded to the upper surface of the flexible electrolyte, and the working electrode is connected to the electrode welding sheet by a metal wire. The counter electrode and the reference electrode are bonded to the lower surface of the flexible electrolyte, and the counter electrode and the reference electrode are distributed on the same vertical line as the through hole of the rigid support partition and the conductive through hole of the bottom shell, and it is ensured that the through hole area of the rigid support partition is larger than the conductive through hole of the bottom shell.
[0105] Example 9
[0106] This embodiment 9 provides a method for preparing a flexible electrolyte, which specifically comprises the following steps: pouring 10 g of hydroxypropyl cellulose into 120 mL of ethanol solvent and stirring overnight to obtain a polymer framework precursor; then pouring the polymer framework precursor into a mold and evaporating part of the solvent to obtain a gel-like substance. The gel-like substance is transferred to a molding device and the ethanol is removed by supercritical carbon dioxide drying to obtain a polymer framework.
[0107] 0.1 g of Co(SCN)2 was dissolved in 2.5 g of 1-ethyl-3-methylimidazole thiocyanate to obtain a mixed solution, and the mixed solution was used to soak the polymer framework to achieve absorption equilibrium to obtain a flexible electrolyte. In this embodiment, the soaking time was 24 hours.
[0108] This embodiment also provides a flexible electrolyte, which is prepared according to the method for preparing a flexible electrolyte.
[0109] This embodiment also provides an application of the above-mentioned flexible electrolyte, which can be used to prepare an ammonia electrochemical gas sensor.
[0110] This embodiment also provides an ammonia electrochemical gas sensor, which is prepared by using the flexible electrolyte.
[0111] Specifically, the structure of the ammonia electrochemical gas sensor provided in this embodiment is the same as that in Embodiment 1.
[0112] Specifically, the preparation steps of the ammonia electrochemical gas sensor include: adding a dispersant to a precious metal catalyst to form a slurry, printing the slurry onto the surface of a hydrophobic breathable membrane, and sintering the slurry to obtain a hydrophobic breathable membrane containing a working electrode, a counter electrode, and a reference electrode, and using a thermal transfer process to transfer the working electrode to the upper surface of a flexible electrolyte, and to transfer the counter electrode and the reference electrode to the lower surface of the flexible electrolyte, respectively, to obtain an electrode-electrolyte integrated structure. The sensor working electrode is bonded to the upper surface of the flexible electrolyte, and the working electrode is connected to the electrode welding sheet by a metal wire. The counter electrode and the reference electrode are bonded to the lower surface of the flexible electrolyte, and the counter electrode and the reference electrode are distributed on the same vertical line as the through hole of the rigid support partition and the conductive through hole of the bottom shell, and it is ensured that the through hole area of the rigid support partition is larger than the conductive through hole of the bottom shell.
[0113] Comparative Example 1
[0114] This comparative example 1 provides a method for preparing a flexible electrolyte, which specifically comprises the following steps: pouring 10 g of hydroxypropyl cellulose into 120 mL of ethanol solvent and stirring overnight to obtain a polymer framework precursor; then pouring the polymer framework precursor into a mold and volatilizing part of the solvent to obtain a gel-like substance. The gel-like substance is transferred to a molding device and the ethanol is removed by supercritical carbon dioxide drying to obtain a polymer framework.
[0115] The polymer framework was immersed in 2.5 g of 1-ethyl-3-methylimidazole thiocyanate to allow absorption equilibrium to be obtained to obtain a flexible electrolyte. In this comparative example 1, the immersion time was 24 hours.
[0116] This comparative example also provides a flexible electrolyte, which is prepared according to the method for preparing a flexible electrolyte.
[0117] This comparative example also provides an application of the above-mentioned flexible electrolyte, and the flexible electrolyte can be used to prepare an ammonia electrochemical gas sensor.
[0118] This comparative example also provides an ammonia electrochemical gas sensor, which is prepared by using the flexible electrolyte.
[0119] Specifically, the structure of the ammonia electrochemical gas sensor provided in this comparative example 1 is the same as that of Example 1. Specifically, it includes a bottom shell 9, an upper shell 2 arranged on the top of the bottom shell 9, the hard support partition 7 arranged inside the bottom shell 9, and a flexible electrolyte 4 arranged on the hard support partition 7. A working electrode 3 is arranged on the upper surface of the flexible electrolyte 4. A counter electrode 5 is arranged alone on the lower surface of the flexible electrolyte 4, or a counter electrode 5 and a reference electrode 6 are arranged at the same time. Conductive through holes are respectively provided on the upper shell 2, the hard support partition 7 and the bottom shell 9, and the working electrode 3 is connected to an electrode welding sheet 10 through a wire. A dustproof film 1 is arranged on the top of the upper shell 2. Among them, the bottom shell 9 and the upper shell 2 are both cylindrical, the working electrode is circular, and the counter electrode and the reference electrode are both semicircular.
[0120] Specifically, the preparation steps of the ammonia electrochemical gas sensor include: adding a dispersant to a precious metal catalyst to form a slurry, printing the slurry onto the surface of a hydrophobic breathable membrane, and sintering the slurry to obtain a hydrophobic breathable membrane containing a working electrode, a counter electrode, and a reference electrode, and using a thermal transfer process to transfer the working electrode to the upper surface of a flexible electrolyte, and to transfer the counter electrode and the reference electrode to the lower surface of the flexible electrolyte, respectively, to obtain an electrode-electrolyte integrated structure. The sensor working electrode is bonded to the upper surface of the flexible electrolyte, and the working electrode is connected to the electrode welding sheet by a metal wire. The counter electrode and the reference electrode are bonded to the lower surface of the flexible electrolyte, and the counter electrode and the reference electrode are distributed on the same vertical line as the through hole of the rigid support partition and the conductive through hole of the bottom shell, and it is ensured that the through hole area of the rigid support partition is larger than the conductive through hole of the bottom shell.
[0121] Performance Testing:
[0122] Sensor signal response test:
[0123] The sensor signal response test was performed on the ammonia sensors prepared in Examples 1 to 3, Examples 6 to 7, Examples 8 to 9 and Comparative Example 1. The specific test steps are as follows: After the ammonia sensor was aged for 3 days, it was subjected to a response performance test in a dynamic atmosphere of 50 ppm ammonia (150 mL / min) to examine the sensor signal response. Figure 7 It can be seen that although the ammonia sensor prepared without adding CuSCN has a response current in an ammonia atmosphere, the current decay phenomenon occurs after being immersed for a long time.
[0124] The test results are as follows Figure 4 , Figure 5 , Figure 6 , Figure 7 , Figure 8 , Fig. 9 , Fig.10 , Fig.11 And as shown in Table 1.
[0125] Table 1
[0126]
[0127]
[0128] from Figure 4 , Figure 5 and Figure 6 From the comparison, we can know that the more CuSCN content in the electrolyte, the greater the response signal under the same gas concentration, that is, the higher the sensitivity, and the addition of CuSCN also improves the current decay problem in the ionic liquid electrolyte. Analysis shows that these advantages are mainly due to the fact that CuSCN can effectively coordinate with NH3, which not only increases the physical solubility of NH3 in the electrolyte and increases the sensitivity of the sensor, but also occupies the lone pair electrons in NH3 to avoid combining with the mobile ions, thereby improving the current decay of the sensor in NH3.
[0129] From the comparison of the results of Example 3 and Comparative Example 1, it can be seen that when the content of CuSCN in the electrolyte increases from 0g to 0.1g, the sensitivity of the sensor also increases from about 95.2nA / ppm to about 181nA / ppm, a significant increase of 85.8nA / ppm, so the addition of CuSCN can enhance the interaction between the electrolyte and the gas, thereby improving the sensitivity of the sensor. In addition to the improvement in sensitivity, after the content of CuSCN increases from 0 to 0.1g, the current attenuation of the sensor also decreases from 10.1% to 0%, which proves that the CuSCN in the electrolyte can effectively prevent the action of ammonia and migrating ions.
[0130] from Figure 6 and Figure 7 , Figure 8 From the comparison, we can know that when the mass ratio of polymer to ionic liquid is 10:1, the sensor sensitivity is relatively low, 132.8nA / ppm, and the current decay is 0%; when the ionic liquid content increases to 4:1, the sensor sensitivity increases significantly to 181.6nA / ppm, and the current decay is also 0%; when the ionic liquid content increases again to 5:2, the sensor sensitivity only increases slightly to 188.0nA / ppm, and the current decay is 4.2%. Therefore, the appropriate ionic liquid content can make the sensor have higher sensitivity and avoid current decay.
[0131] Depend on Figure 6 and Fig. 9 , Fig.10It can be seen from the comparison that the type of transition metal salt in the electrolyte has a great influence on the performance of the sensor. When the transition metal salt is CuSCN, the sensor sensitivity is improved the most, reaching 181.6nA / ppm, and no current decay occurs; when the type of transition metal salt is changed to Ni(SCN)2, the sensor sensitivity is only 104nA / ppm, and the current decay is 9.2%; when the transition metal salt is changed to Co(SCN)2, the sensor sensitivity is even smaller, at 100.8nA / ppm, and the current decay is 9.5%. From the analysis of the coordination constants of different transition metal ions, it is believed that: Ni 2+ The coordination constant with NH3 is 8.74, Co 2+ The coordination constant with NH3 is 5.11, Cu + The coordination constant with NH3 is 10.86. From the data, it can be seen that the addition of metal ions that can coordinate with NH3 can increase the sensitivity of the sensor. 2+ With Co 2+ The coordination constant is smaller than H + NH3 is 9.25, so NH3 is still mainly related to H + Coordination, resulting in a decrease in the migration speed of the migrating ions and a decrease in the H + As the concentration decreases, the reduction rate slows down, thus failing to improve the current decay. + The coordination constant with NH3 is slightly greater than that with NH4 + The stability constant can avoid NH4 + The formation of Cu(NH3)2SCN and the coordination constant are relatively suitable, so it can slowly recover from Cu(NH3)2SCN to CuSCN in the electrolyte. Therefore, the coordination with NH3 is reversible, which can improve the current attenuation in the ammonia atmosphere.
[0132] In summary, the electrode-electrolyte integrated structure and ammonia sensor provided by the present invention can effectively improve the miniaturization process of the sensor and improve the current attenuation problem of the electrode-electrolyte integrated structure.
[0133] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that the specific implementation methods of the present invention can still be modified or some technical features can be replaced by equivalents without departing from the spirit of the technical solution of the present invention, which should be included in the scope of the technical solution for protection of the present invention.
Claims
1. A flexible electrolyte for preparing an ammonia electrochemical gas sensor, characterized in that: It is prepared from ionic liquid, polymer containing polar groups and transition metal salt; The transition metal salt is CuSCN; The polar group-containing polymer includes hydroxyethyl cellulose, hydroxypropyl cellulose, cellulose acetate, PAA or PMAA.
2. The flexible electrolyte according to claim 1, characterized in that: The ionic liquid is 1-ethyl-3-methylimidazole thiocyanate, 1-propyl-3-methylimidazole thiocyanate, 1-butyl-3-methylimidazole thiocyanate, 1-hexyl-3-methylimidazole thiocyanate, 1-octyl-3-methylimidazole thiocyanate, 1-decyl-3-methylimidazole thiocyanate, 1-dodecyl-3-methylimidazole thiocyanate, 1-tetradecyl-3-methylimidazole thiocyanate, 1-hexadecyl-3-methylimidazole thiocyanate, 1-butyl-2,3-dimethylimidazole thiocyanate, 1-vinyl-3-propylimidazole thiocyanate, 1-vinyl-3-butylimidazole thiocyanate, 1-vinyl-3-benzylimidazole thiocyanate, 1-ethyl-3-methylimidazolium cyanamide, 1-butyl-3-methylimidazolium dicyanamide, 1-hexyl-3-methylimidazolium dicyanamide, 1-ethyl-3-methylimidazolium hydrogen sulfate, 1-butyl-3-methylimidazolium hydrogen sulfate, 1-hexyl-3-methylimidazolium hydrogen sulfate, 1-butyl-2,3-dimethylimidazolium hydrogen sulfate, 1-hexyl-2,3-dimethylimidazolium hydrogen sulfate, 1-methylimidazolium hydrogen sulfate, 1-ethylimidazolium hydrogen sulfate, 1-butylimidazolium hydrogen sulfate, 1-hexylimidazolium hydrogen sulfate, 1-vinyl-3-propylimidazolium hydrogen sulfate, 1-vinyl-3-butylimidazolium hydrogen sulfate or 1-hydroxyethyl-3-methylimidazolium hydrogen sulfate.
3. The flexible electrolyte according to claim 1, characterized in that: The polymer containing polar groups is hydroxypropyl cellulose; The ionic liquid is 1-ethyl-3-methylimidazole thiocyanate.
4. The flexible electrolyte according to claim 1, characterized in that: The mass ratio of the polar group-containing polymer, the ionic liquid, and the transition metal salt is 100:(20-80):(0.02-16).
5. A method for preparing a flexible electrolyte as claimed in claim 1, characterized in that: The following steps are involved: The polymer containing polar groups is dissolved, molded and dried to obtain a polymer frame, and the polymer frame is soaked in an ionic liquid dissolved with a transition metal salt until absorption equilibrium is reached to obtain a flexible electrolyte; The polar group-containing polymer includes hydroxyethyl cellulose, hydroxypropyl cellulose, cellulose acetate, PAA, PMAA; The transition metal salt is CuSCN.
6. The method for preparing a flexible electrolyte according to claim 5, characterized in that: The mass ratio of the polar group-containing polymer, the ionic liquid, and the transition metal salt is 100:(20-80):(0.02-16).
7. The method for preparing a flexible electrolyte according to claim 5, characterized in that: The ionic liquid is 1-ethyl-3-methylimidazole thiocyanate, 1-propyl-3-methylimidazole thiocyanate, 1-butyl-3-methylimidazole thiocyanate, 1-hexyl-3-methylimidazole thiocyanate, 1-octyl-3-methylimidazole thiocyanate, 1-decyl-3-methylimidazole thiocyanate, 1-dodecyl-3-methylimidazole thiocyanate, 1-tetradecyl-3-methylimidazole thiocyanate, 1-hexadecyl-3-methylimidazole thiocyanate, 1-butyl-2,3-dimethylimidazole thiocyanate, 1-vinyl-3-propylimidazole thiocyanate, 1-vinyl-3-butylimidazole thiocyanate, 1-vinyl-3-benzylimidazole thiocyanate, 1-ethyl-3-methylimidazolium cyanamide, 1-butyl-3-methylimidazolium dicyanamide, 1-hexyl-3-methylimidazolium dicyanamide, 1-ethyl-3-methylimidazolium hydrogen sulfate, 1-butyl-3-methylimidazolium hydrogen sulfate, 1-hexyl-3-methylimidazolium hydrogen sulfate, 1-butyl-2,3-dimethylimidazolium hydrogen sulfate, 1-hexyl-2,3-dimethylimidazolium hydrogen sulfate, 1-methylimidazolium hydrogen sulfate, 1-ethylimidazolium hydrogen sulfate, 1-butylimidazolium hydrogen sulfate, 1-hexylimidazolium hydrogen sulfate, 1-vinyl-3-propylimidazolium hydrogen sulfate, 1-vinyl-3-butylimidazolium hydrogen sulfate or 1-hydroxyethyl-3-methylimidazolium hydrogen sulfate.
8. The method for preparing a flexible electrolyte according to claim 6 or 7, characterized in that: The polar group-containing polymer is hydroxypropyl cellulose, and the ionic liquid is 1-ethyl-3-methylimidazole thiocyanate; The steps of preparing the polymer framework include: dissolving the hydroxypropyl cellulose in an ethanol solvent, stirring overnight to obtain a polymer framework precursor, and then pouring the polymer framework precursor into a mold to remove the ethanol solvent through a supercritical carbon dioxide drying method to obtain the polymer framework.
9. A flexible electrolyte, characterized in that: The flexible electrolyte is prepared according to the preparation method according to any one of claims 6 to 8, and the flexible electrolyte is a self-supporting, deformable flexible membrane.
10. An integrated electrode electrolyte, characterized in that: It comprises the flexible electrolyte as claimed in claim 9, and an electrode arranged on the surface of the flexible electrolyte by a thermal transfer process.
11. Use of the flexible electrolyte according to claim 9 or the integrated electrode electrolyte according to claim 10 in preparing an ammonia electrochemical gas sensor.
12. An ammonia electrochemical gas sensor comprising the flexible electrolyte of claim 9, characterized in that: It includes a bottom shell, an upper shell arranged on the top of the bottom shell, a hard supporting partition arranged inside the bottom shell, and the flexible electrolyte arranged on the hard supporting partition, the upper surface of the flexible electrolyte is provided with a working electrode, the lower surface of the flexible electrolyte is provided with a counter electrode alone or with a counter electrode and a reference electrode at the same time, the upper shell, the hard supporting partition and the bottom shell are respectively provided with conductive through holes, the working electrode is connected to an electrode welding sheet through a wire, and a dustproof film is provided on the top of the upper shell.
Citation Information
Patent Citations
Electrochemical gas sensors with ionic liquid electrolyte systems
CN103926306A
Membranes for use in electrochemical sensors and associated devices
US20160146751A1